Inclusión en las Sentencias Condenatorias emitidas por los Jueces de Garantías Penales, a más de la Sanción, la Indemnización por Daños y Perjuicios - Jumbo Cedillo, Máximo Cristóbal (2017)
The present so called research work: "Inclusion In The Condemnatory Judgments Expressed By The Judges Of Penal Guarantees, To More Of The Sanction, The Indemnification For Dammages”, it has realized bearing in mind the contents table with the delimited topics that previously I have realized. It is for it that in the conceptual frame we find the explanations of the concepts, the evolution and the comprehension of the intentions that we have about the indemnification of the dammages, as well as also the faculty that the judges of penal guarantees have to fix the total of the indemnification in the penal judgment, taking in consideration the emergent damage, the dismissed lucre, the material damage, and the immaterial damage. Across the juridical frame there has been analyzed the Constitution of the Republic of the Ecuador in the part that treats on the rights and you were guaranteeing, that is to say in its dogmatic and organic part. Across the penal Integral Organic Code the defenselessness of the victims is investigated after the indemnification is not included by dammages in the judgment expressed by the judges of penal guarantees and across the Civil Code we can realize the effects that have the obligations and especially the importance that has the emergent damage and the dismissed lucre inside the indemnification as dammages. 5 In the doctrinaire frame the analysis is punctual because it treats the constitutional beginning, the consequences that take place in the accused and especially in the victim and the effects that the inclusion of the indemnification will produce for dammages in the judgments that the different penal courts express. Likewise we have studied the doctrine of different commentators and the personal criterion of the investigator on the expediency of including in the judgment that the penal judges express the indemnification for dammages to the victim of a crime. This investigation proposes to bring near norms that agree with the beginning of the justice that guarantees the Constitution of the Republic of the Ecuador, but in case of the inclusion of the indemnification for dammages in the judgment that the penal judges express it will facilitate the juridical safety of the victims of a crime. The field investigation has demonstrated that our proposal must be attended by the National Assembly so that the victim of a crime is indemnified in the same judgment that expresses the penal courts. Finally the conclusions and recommendations are the product of the application of the scientific method that treats the most outstanding points of this investigation.